Production performance of hydraulic fractures in tight gas sands, a numerical simulation approach. Journal of Petroleum Science and Engineering - Ostojic, Jakov; Rezaee, R; Bahrami, Hassan (Elsevier BV, 2012)
Hydraulically fractured tight gas reservoirs are one of the most common unconventional gas sources being produced today, and will be a regular source of gas in the future. The extremely low permeability of tight gas sands leads to inaccuracy of conventional build-up and draw-down well test results. This is primarily due to the increased time required for transient flow in tight gas sands to reach pseudo-steady state condition. To increase accuracy, well tests for tight gas reservoirs must be run for longer periods of time which is in most cases not economically viable. The large amount of downtime required to conduct well tests in tight sands makes them far less economical than conventional reservoirs, which leads to the need for accurate simulation of tight gas reservoir well tests. This paper presents simulation results of a 3-D hydraulically fractured tight gas model created using Eclipse software. The key aims are to analyze the effect of differing fracture orientation, number and length. The focus of the simulation runs will be on the effect of hydraulic fracture orientation and length. The results will be compared to simulation runs without the abovementioned factors to determine their effects on production rates and well performance analysis. All results are plotted alongside an un-fractured tight gas scenario in order to put the hydraulic fracture performance in perspective. Key findings from this work include an approximately linear relationship between initial gas rate and the number of hydraulic fractures intersecting the wellbore. In addition, fracture length is found to have less of an impact on initial gas rate compared to number of fractures intersecting the wellbore, for comparable total fracture volumes.